2002
DOI: 10.1645/0022-3395(2002)088[0244:usoted]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Study of the Early Development and Localization of Loma Salmonae in the Gills of Experimentally Infected Rainbow Trout

Abstract: The early ultrastructural stages of Loma salmonae were studied in the gills of experimentally infected rainbow trout. No parasitic stages were identified during the first 2 wk of the infection. By week 3 postexposure (PE), uninucleate and binucleate meronts were recognized within host cells (no xenomas) associated with the capillary channels of secondary lamellae and lamellar arteries. An inflammatory reaction was absent. In secondary lamellae, infected cells were isolated from the capillary lumen, and some we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…They include parasite migration (Buchmann et al, 2001) and exploitation of the host immune system (Buchmann, 2000). Other parasites have shown evasion mechanisms based on antigen variation or mimicry, modification of the host's immune system, resistance to host's cellular (Rodriguez-Tovar et al, 2002) or humoral factors through, for example, the development of a thick parasite tegument containing inhibitors of the complement cascade (Buchmann and Lindenstrøm, 2002).…”
Section: Evasion Processmentioning
confidence: 99%
“…They include parasite migration (Buchmann et al, 2001) and exploitation of the host immune system (Buchmann, 2000). Other parasites have shown evasion mechanisms based on antigen variation or mimicry, modification of the host's immune system, resistance to host's cellular (Rodriguez-Tovar et al, 2002) or humoral factors through, for example, the development of a thick parasite tegument containing inhibitors of the complement cascade (Buchmann and Lindenstrøm, 2002).…”
Section: Evasion Processmentioning
confidence: 99%
“…For instance, in a series of studies aiming to elucidate the tissue reaction in rainbow trout, Oncorhynchus mykiss, experimentally exposed to infective spores of Loma salmonae, it was observed that infected cells were identified as blood cells. These cells were probably retained in lamellar capillaries due to their enlargement, as well as pillar cells and possibly leukocytes lying between the endothelium and the basement membrane of lamellar arteries [38]. In the same research, an early weak inflammatory response characterized by spore destruction within xenomas was observed at week four after exposure.…”
Section: Host Reaction To Xenomasmentioning
confidence: 65%
“…This might be explained by differences in the cell responses between the early stages of infection (1-4 weeks PE), which are more subtle than the cell responses during later stages of infection (5-10 weeks PE), which are associated with disease. In MGD, little host response is seen to the development of xenomas during the early stages of xenoma maturation (Rodriguez-Tovar et al 2002). Beginning at 5 weeks PE and continuing into 10 weeks PE, the rupture of xenomas is associated with a heavy inflammatory response, and during this time, clinical disease is apparent (Lovy et al 2007;Rodriguez-Tovar et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…During MGD, infection with L. salmonae occurs across the gastrointestinal tract, and at 2 weeks postexposure (PE), the parasite arrives in the gills and forms parasitic cysts called xenomas (Rodriguez-Tovar et al 2002;Sanchez et al 2001). Xenomas expand in size as the parasites replicate until around 6-9 weeks PE when the xenomas rupture liberating spores into the gill tissue leading to a severe inflammatory response (Lovy et al 2007).…”
Section: Introductionmentioning
confidence: 99%